2019
DOI: 10.1136/neurintsurg-2019-015247
|View full text |Cite
|
Sign up to set email alerts
|

A 10% blood pressure drop from baseline during mechanical thrombectomy for stroke is strongly associated with worse neurological outcomes

Abstract: BackgroundMechanical thrombectomy (MT) for acute ischemic stroke can be performed under local anesthesia, with or without conscious sedation (CS), or under general anesthesia (GA). The hemodynamic consequence of anesthetic drugs may explain why GA may be associated with worse outcomes. We evaluated the association between hypotension duration during MT and the 90 day functional outcome under both anesthetic regimens.MethodsPatients were included in this retrospective study if they had an ischemic stroke treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 43 publications
4
35
1
1
Order By: Relevance
“…sICH rates were not significantly related to baseline systolic or diastolic blood pressure (93). Systolic, pulse pressure and mean arterial BP variability during EVT seem to be critically associated with functional outcome (91,92,(95)(96)(97)(98), but data are scarce regarding the association of blood pressure variability during EVT and sICH risk. After EVT, and notably after complete reperfusion, blood pressure variability seems associated with increased rates of sICH (99,100).…”
Section: The Issue Of Blood Pressure In Evt-treated Patientsmentioning
confidence: 95%
“…sICH rates were not significantly related to baseline systolic or diastolic blood pressure (93). Systolic, pulse pressure and mean arterial BP variability during EVT seem to be critically associated with functional outcome (91,92,(95)(96)(97)(98), but data are scarce regarding the association of blood pressure variability during EVT and sICH risk. After EVT, and notably after complete reperfusion, blood pressure variability seems associated with increased rates of sICH (99,100).…”
Section: The Issue Of Blood Pressure In Evt-treated Patientsmentioning
confidence: 95%
“…Similar, previous studies reported worse functional outcomes in patients with a drop in MAP from baseline of ≥ 10% who received CS or GA during the procedure. 14,19,28 A recent study found that larger AUTs were associated with worse functional outcome in patients receiving GA as well as in patients receiving monitored anesthesia care (MAC), which is a composite of CS and LA. 7 In our study, blood pressure drops were relatively mild, especially in…”
Section: A C C E P T E D Discussionmentioning
confidence: 99%
“…Because there is no consensus on which BP-derived measures are most relevant and what should be avoided (e.g., drops, variability), we focused on 3 predefined orthogonal definitions that capture different elements of BP drops and variability 17 : area under the threshold (AUT, with MAP on admission as the threshold determined per patient) in mm Hg*minute, reflecting both the depth and duration of the relative hypotensive episode; the relative difference between the MAP on admission and the lowest MAP during the EVT procedure, expressed as percentage drop in MAP (∆LMAP), to account for shorter, larger BP drops; and the BP trend during the procedure, defined as the slope for each patient derived from a multilevel linear regression model with “time since start procedure” as a predictor, with a random slope to estimate patient-specific trends in BP measurements, for the continuous outcome systolic BP including a random effect for patient to account for within-patient variability ( figure 1 ). 7 , 8 , 18 20 Hemodynamic intervention was defined as the administration of any inotropes or vasopressors (e.g., ephedrine, phenylephrine) to increase BP or the use of sympathicolytics (e.g., labetalol, clonidine) to lower BP. BP was regulated according to institutional practices; in general, systolic BP was maintained between 140 and 185 mm Hg with a diastolic BP below 105 mm Hg based on anesthetic critical care recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant BP drop may occur during the induction phase of GA during MT, since a drop in BP is a side effect of most anesthetic medications [96]. However, not only GA but also CS causes a decline in BP [97,98] (see above).…”
Section: Low Blood Pressure In Aismentioning
confidence: 99%